2017
DOI: 10.1002/chir.22769
|View full text |Cite
|
Sign up to set email alerts
|

Fast liquid chromatography for racemic atenolol acetate separation—The analytical protocol

Abstract: Kinetic resolution of (R,S)-atenolol is a faster strategy to produce (S)-atenolol. Since this racemate is a less soluble compound, resolution of its ester offers high concentrations in the process. A good analytical method is required to observe the enantiomer concentrations. This paper described application of ultra-fast liquid chromatography on the atenolol ester separation using different resolution media and analytical procedures. Chiralcel OD column resolved the ester. The chromatograms indicated differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…During the course of the reaction, the enantioselectivity gradually decreased and PFL exhibited non-selective behaviour. In a recent study on kinetic resolution of racemic atenolol, PFL has been reported to give (S)-enantiomer in 24 h. 36 In another study, PFL catalyzed the kinetic resolution of some novel antifungal Nsubstituted benzimidazole derivatives in more than 72 h. 37 Thus, the rapid action of PFL on (RS)-4 with high degree of enantioselectivity and rate of conversion reported here is suggestive of strong interaction between (RS)-4 and PFL, thereby revealing a better chemoenzymatic process that could be used for the synthesis of enantiopure metoprolol in a shorter time.…”
Section: Effect Of Reaction Timementioning
confidence: 99%
“…During the course of the reaction, the enantioselectivity gradually decreased and PFL exhibited non-selective behaviour. In a recent study on kinetic resolution of racemic atenolol, PFL has been reported to give (S)-enantiomer in 24 h. 36 In another study, PFL catalyzed the kinetic resolution of some novel antifungal Nsubstituted benzimidazole derivatives in more than 72 h. 37 Thus, the rapid action of PFL on (RS)-4 with high degree of enantioselectivity and rate of conversion reported here is suggestive of strong interaction between (RS)-4 and PFL, thereby revealing a better chemoenzymatic process that could be used for the synthesis of enantiopure metoprolol in a shorter time.…”
Section: Effect Of Reaction Timementioning
confidence: 99%
“…Surface-modified silica gel-based particles proved to be efficient supports in our practice for the immobilization of several lipases [21][22][23][24][25][26]. Therefore, in this study our aim was to extend the immobilization of further lipases [Lipase AK from Pseudomonas fluorescens (Lipase AK), Lipase PS from Burkholderia cepacia (Lipase PS) and Lipase from Candida rugosa (CrL)] using bisepoxide-activated mesoporous hollow silica microspheres to produce efficient biocatalysts for kinetic resolution of secondary alcohols.…”
Section: Introductionmentioning
confidence: 99%